STUDI KELAYAKAN PENGEMBANGAN APLIKASI SATU PINTU MENGGUNAKAN COST-BENEFIT ANALYSIS PADA START UP SATU PINTU - Ravika Ayu Ashari; Erwin Sutomo; Vivine Nurcahyawati (Jurnal Sistem Informasi Universitas Dinamika, 2021)
Startups are often associated with companies engaged in information technology, including Satu Pintu whose business processes use information technology. However, the development of information technology projects requires a lot of money, especially Satu Pintu is a new startup that is still in the pioneering stage and still does not have a broad scope.Therefore, One Stop requires a feasibility study analysis related to the development of a One Stop application project with the aim of knowing the feasibility of the application being developed and marketed or not. To avoid the risk of investing too much, but the benefits obtained are not comparable to those invested, therefore this feasibility study will be viewed from an economic point of view using the Cost Benefit Analysis method to identify and calculate the cost benefits of developing the One Stop application, to analyze the costs incurred The method used is Use Case Points, while to analyze the benefits of IS / IT development using the Ranti's Generic IS / IT Value method in its identification.The results obtained after an analysis using several methods, show that the One Door application development has a benefit ratio of 3 times greater than the investment that must be spent. There are several things that One Pintu must pay attention to, namely that investment in application development has not been able to return the value of the initial capital of 5% and the payback period will return within 1 year. From the above analysis, it can be concluded that the company needs to conduct periodic analysis to analyze the absorption of benefits and costs to determine the value of the discount rate and interest rate and the company must also avoid changing conditions in the company's condition of more than 5% to avoid the feasibility risk of developing the One Stop application.